A Comparative Study of Turbulence Models on Aerodynamics Characteristics of a NACA0012 Airfoil - Sadikin, Azmahani; Mohd Yunus, Nurul Akma; Abd Hamid, Saiful Anuar; Ismail, Al Emran; Md Salleh, Salihatun; Abdol Rahman, Mohd Nasrull; Mahzan, Shahruddin; Ayop, Sallehuddin Shah (International Journal of Integrated Engineering, 2018)
This paper presented a computational fluid dynamics (CFD) simulation of air flow past a 2D model NACA0012 airfoil at high Reynolds number (Re = 3.0 x 106) at various angles of attack (-10° to 15°). The simulations were undertaken to inform on how the fluid flowed around the airfoil by solving the steady state governing equations of continuity and momentum conservation that are combined with one of three turbulence models Spalart-Allmaras, Realizable k-ε and k-ω shear stress transport (SST). It is observed that the Realizable k- ε eliminates the small separation bubble on the upper surface of the airfoil and delaying separation flow. Also, for the lift coefficient, CL and drag coefficient, CD investigated in this paper, the predicted data have good agreement with other published data.